Polarization Converter with Controllable Birefringence Based on Hybrid All-Dielectric-Graphene Metasurface - Owiti, Edgar O; Yang, Hanning; Liu, Peng; Ominde, Calvine F (Nanoscale Research Letters, 2018)
Previous studies on hybriddielectric-graphenemetasurfaceshavebeenusedtoimplementinducedtransparency devices,while exhibiting high Q-factors based on trapped magnetic resonances.Typically,the transparencywindows are singlewavelengthandlessappropriateforpolarizationconversionstructures.Inthiswork,aquarter-waveplate based onahybridsilicon-graphenemetasurfacewithcontrollablebirefringenceisnumericallydesigned.The phenomena oftrappedmagneticmoderesonanceandhighQ-factorsaremodulatedbyinsertinggraphenebetween silicon andsilica.Thisresultsinabroadertransmissionwavelengthincomparisontotheall-dielectricstructure without graphene.ThebirefringencetunabilityisbasedonthedimensionsofsiliconandtheFermienergyof graphene.Consequently,alinear-to-circularpolarizationconversionisachievedatahighdegreeof96%,inthe near-infrared.Moreover,the polarization state of the scattered light is switch able between right and left hand circular polarizations,based on an external gate biasing voltage.Unlike in plasmonic metasurfaces,these achievements demonstrate an efficient structure that is free from radiative and ohmic losses.Furthermore,the ultra thin thickness and the compactnessofthestructurearedemonstratedaskey components in realizing integrable and CMOS compatible photonic sensors.
Keywords: Metasurfaces; Polarization converter; All-dielectric/graphene; Birefringence